Improved Genome Assembly and Annotation of the Soybean Aphid (Aphis glycines Matsumura) - Mathers, Thomas C. (G3 (Bethesda), 2020)
Aphids are an economically important insect group due to their role as plant disease vectors. Despite this economic impact, genomic resources have only been generated for a small number of aphid species. The soybean aphid (Aphis glycines Matsumura) was the third aphid species to have its genome sequenced and the first to use long-read sequence data. However, version 1 of the soybean aphid genome assembly has low contiguity (contig N50 = 57 Kb, scaffold N50 = 174 Kb), poor representation of conserved genes and the presence of genomic scaffolds likely derived from parasitoid wasp contamination. Here, I use recently developed methods to reassemble the soybean aphid genome. The version 2 genome assembly is highly contiguous, containing half of the genome in only 40 scaffolds (contig N50 = 2.00 Mb, scaffold N50 = 2.51 Mb) and contains 11% more conserved single-copy arthropod genes than version 1. To demonstrate the utility of this improved assembly, I identify a region of conserved synteny between aphids and Drosophila containing members of the Osiris gene family that was split over multiple scaffolds in the original assembly. The improved genome assembly and annotation of A. glycines demonstrates the benefit of applying new methods to old data sets and will provide a useful resource for future comparative genome analysis of aphids.